Carbapenem-resistant Enterobacterales bloodstream infections related to death in two Brazilian tertiary hospitals - Lorena Galvão de Araujo; Kehvyn Cedeño; Adriele Pinheiro Bomfim; Marcio de Oliveira Silva; Ana Verena Mendes; Maria Goreth Barberino; Edilane Lins Gouveia; Fabianna Márcia M. Bahia; Mitermayer Galvão dos Reis; Joice Neves Reis (BMC Infectious Diseases)
Abstract Background Bloodstream infection (BSI) caused by carbapenem-resistant Enterobacterales (CRE) is a major global public health concern due to its high lethality and limited treatment options. In Brazil, CRE was first reported in 2005, with Klebsiella pneumoniae carbapenemase (KPC) documented in 2009. Despite ongoing reports, data remain limited in several regions. Objective To describe the lethality rate and epidemiological and clinical characteristics of BSI patients with Enterobacterales BSI and assess carbapenem resistance to identify major risk factors for CRE infection and lethality. Methods This prospective laboratory-based surveillance study, which was conducted in two tertiary hospitals (April 2016–December 2018), analyzed BSI cases caused by Enterobacterales. Clinical and demographic data were obtained from medical records. The bacterial isolates were identified by mass spectrometry and by VITEK-2®, with antimicrobial susceptibility testing performed by VITEK-2®. Logistic regression and Kaplan‒Meier survival analyses were used to assess the impact of CRE BSI on death. Results Among 252 patients with enterobacterial BSIs were identified, of which 14.3% had CRE. The overall lethality rate was 37.7%. Compared with carbapenem-susceptible Enterobacterales, CRE-associated BSIs were associated with significantly greater lethality (71.6% vs. 28.4%; p < 0.001; OR = 6.53, 95% CI [3.01–15.41]). The association remained significant after adjusting for age, comorbidities, Pitt bacteremia score, Enterobacterales species, BSI type, and sepsis. All CRE BSI cases were hospital-acquired. Conclusions CRE accounts for 14.3% of BSIs and is strongly associated with increased lethality. Given the limited epidemiological data in Brazil, this study provides valuable epidemiological insights that may inform local treatment protocols for Enterobacterales infections.